2019
DOI: 10.1038/s41598-019-50693-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from 3-month-old infants shows that a combination of postnatal feeding and exposures in utero shape lipid metabolism

Abstract: We tested the hypothesis that both postnatal feeding and conditions in utero affect lipid metabolism in infants. Infants who experienced restrictive growth conditions in utero and others exposed to maternal hyperglycaemia were compared to a control group with respect to feeding mode. Dried blood spots were collected from a pilot subset of infant participants of the Cambridge Baby Growth Study at 3mo. Groups: (a) a normal gestation (control, n = 40), (b) small for gestational age (SGA, n = 34) and (c) whose mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Discovery of candidate biomarkers (CBMs) is an established technique for identifying the variables that both distinguish two groups and drive the statistical difference between them [13,16,24,26]. This involves running a sparse partial least squares discriminant analysis [35] followed by a student's t test with a significance threshold adjusted for multiple variables and/or comparisons as appropriate.…”
Section: Lipidome Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Discovery of candidate biomarkers (CBMs) is an established technique for identifying the variables that both distinguish two groups and drive the statistical difference between them [13,16,24,26]. This involves running a sparse partial least squares discriminant analysis [35] followed by a student's t test with a significance threshold adjusted for multiple variables and/or comparisons as appropriate.…”
Section: Lipidome Analysismentioning
confidence: 99%
“…There is mounting evidence that lipid metabolism has a crucial role in growth and metabolic disease in humans [12][13][14][15][16]. This has encouraged the development of methods required for lipid profiling.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the serious risk to their metabolic health, obesity in both men and women has long-term consequences for their offspring through nutritional programming 1 3 . There is increasing evidence showing that the nutritional programming of offspring occurs through changes in lipid metabolism 4 and leads to increased risk of cardio-metabolic disease 5 9 . One contributor to obesity is excess carbohydrate intake.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of a cohort not selected for BMI found evidence for shifts in lipid metabolism associated with GDM, at a molecular level. 28,29 We have also characterised the early second trimester lipoprotein profile in obese pregnancy and GDM and found that the abundance of VLDLs, small LDLs and HDLs differs in women who develop GDM compared to those who do not. 30 Collectively, this evidence suggests that both lipid biosynthesis and distribution are altered in advance of a standard diagnosis of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we profiled the organically-soluble fraction (containing the lipids, glyceride and sterols) using state-of-the-art lipidomics methods on plasma samples collected at 15-18 weeks gestation from the UPBEAT [30][31][32] cohort of obese pregnant women. Molecular profiling involved direct infusion mass spectrometry (DI-MS 28,[33][34][35][36][37] ) with chipbased nanospray, in both positive and negative ionisation modes. A supervised multi-variate analysis (sparse Partial Least Squares-Discriminant Analysis, sPLS-DA) followed by a student's T-test was used to identify lipid molecular species that distinguished participants who were later diagnosed with GDM from those who did not develop GDM, and to identify the variables that drive this distinction.…”
Section: Introductionmentioning
confidence: 99%